Transformed by Parenting Experience: Perspectives, Challenges, and Optimism of Parents of Children with Autism Spectrum Disorder in Their Adulthood - Pacis, Cecille Marie (Eximia, 2023)
Background. Parenting a child with autism spectrum disorder comes with many insights, challenges, and seeing the silver lining from experience. Parents with children under the spectrum are exposed to much exhaustion. As unique as the characteristic of the child’s disability, they all have different types of struggles. The researcher is a special needs teacher who has handled children with different types of disabilities and bonded with their parents over the years. Although their experiences have similar patterns, they have unique insights that many fail to see. Furthermore, the researcher, who has a great interest in the parents’ varying visions in life, conducted a study to dig deeper into their experiences, troubles, and how their life encounters are extraordinarily exceptional compared to regular parents. The paper explores their life dynamics, mindset, skills, and realizations through qualitative phenomenological lenses. Methods. The qualitative research approach and phenomenology were utilized to explore and understand the unique experiences of parents raising their children with autism in adulthood. The process of the study involved emerging questions and procedures, data typically collected in the participant’s setting, data analysis inductively building from particulars to general themes, and the researcher making interpretations of the meaning of the data. Results. The qualitative data analysis revealed that parents with children with autism in their adolescence follow similar, although not all, experiences from the moment they discover the diagnosis until learning to accept their reality and raising their children. They have similar types of challenges and realizations while raising these children. Unlike some people, when faced with very tough trials in life, they do not have the option to quit their role nor have the liberty to change their situation and steer their path in life in a different direction. Giving up is not in their books, and they continue life as parents and face their challenges head-on. Furthermore, the qualitative data generated three major themes, namely (1) Insights on Parenting of Children with Autism in their Adolescence with five subthemes, (2) Difficulties and Struggles in Parenting a Child with Autism with seven sub-themes, and (3) Seeing the Silver Lining in Being Parents to a Child with ASD with five sub-themes. Conclusion. The journey of parents in raising children with autism comes with varying challenges that are different from the regular parents with typically developing children experience. Generally, parents of children with ASD would start by sharing many endless struggles. Although they will always have similar struggles, each parent has a unique experience with their child’s disability. Their experience is their best teacher in knowing how to cope with their unique struggles, which come in different levels of severity; hence they become braver in facing difficult situations which have to be dealt with no matter what. Parents who have spent more years in their experience in raising a child with ASD, such as in their adolescent years, already have more insights and usually see the silver linings in raising them compared to parents who just started this similar journey. These parents garnered many realizations about themselves and their purpose and became transformed in their lives. Practical Value of the Paper. The study will benefit parents with children with autism or any form of disability who feel uncertain about their journey of raising a child with autism and wonder what the best thing to do for their child is. When they encounter studies like this, they will learn the common patterns of experienced ASD parents, navigate clearer on what to expect, gain useful insights, and have emotional support. They will realize they are not alone and that many other parents are going through the same thing. This is also beneficial for special needs teachers who have first-hand experience with these parents and will have a broader understanding of what they are going through. Understanding what they are going through will help them build a good rapport and make academic planning for their child easier. Directions for Future Research. This study will serve as a baseline for future research on lived experiences of mothers of children with autism. The patterns and other findings about their experiences can be used to enhance further research about family experiences for those who have members with disabilities. They can go beyond the scope of this study and tap into other concerns related to the results. Possible changes or progress could be related to the study, and future researchers can continue the topic with different or better findings. They can recognize the limitations of the current studies on this topic and may add significant revisions for better public involvement.